The Future of Medicine: Harnessing the Power of AI for Revolutionizing Healthcare - Alexandra Harry (International Journal of Multidisciplinary Sciences and Arts, 2023)
Artificial intelligence (AI) has the potential to completely change how healthcare is delivered, revolutionizing the healthcare sector. Precision diagnosis, proactive disease prevention, personalised treatment plans, real-time monitoring and intervention, improved medical imaging, streamlined healthcare workflows, ethical considerations, and the potential future implications of AI in healthcare are all explored in this paper. The first section describes how precision diagnosis using AI technologies is improving diagnostic accuracy. Personalised treatment regimens and earlier disease detection are made possible by machine learning algorithms' analysis of enormous volumes of patient data. Additionally, AI makes it possible to actively prevent disease by using predictive analytics to identify those who are most likely to develop a particular condition, enabling early intervention and tailored preventive actions. The second segment focuses on how AI is transforming therapeutic approaches. AI algorithms create individualised treatment regimens by analyzing patient data, including genetics, biomarkers, and information on therapy response. This maximizes treatment efficacy and minimizes side effects. Additionally, wearable technology and remote monitoring devices powered by AI allow for real-time monitoring and intervention, improving patient safety and lowering hospital readmissions. Examines how AI has affected medical imaging. Radiologists' efficiency and accuracy in identifying anomalies are increased by deep learning algorithms' analysis of complicated medical pictures like CT scans and MRIs. As a result, diagnoses are made more quickly and accurately, allowing for quicker interventions and better patient outcomes. The fourth chapter examines how AI streamlines medical procedures. Administrative responsibilities are reduced and errors are minimized by automating operations like appointment scheduling and documentation. By offering timely support and triaging symptoms, intelligent catboats and virtual assistants increase patient involvement and happiness. The fifth segment talks with ethical issues related to AI in healthcare. In order to create and use AI algorithms responsibly, patient privacy, data security, and bias mitigation are essential. Fair and equitable healthcare practices must be ensured by ethical standards and legal requirements. The abstract wraps off with a preview of the potential effects of AI on healthcare delivery in the future. Emerging medical technologies including telemedicine, robotics, predictive analytics, and AI-assisted surgery show immense promise for revolutionizing the industry. To overcome obstacles, maximize advantages, and guarantee a human-centric approach in the integration of AI in healthcare, cooperation between healthcare practitioners, technologists, policymakers, and ethicists is essential.